The Price and Employment Response of Firms to the Introduction of Minimum Wages - Sebastian Link (Institute of Labor Economics (IZA), 2022)
This paper studies the price and employment response of firms to the introduction of a nation-wide minimum wage in Germany. Widely throughout the economy, affected firms responded by rapidly and frequently increasing prices without cutting employment. These decisions are strongly interrelated: Firms that increased prices relatively more often also showed a less negative employment response. The relative importance of both adjustment margins is associated with product market competition and the specific economic situation firms face during the treatment period. Hence, understanding the role of price pass-through appears to be key for explaining employment effects of minimum wages.
Keywords: E31; E24; J38; J31; 330; minimum wage; price pass-through; employment; interrelation of firms' choices